2018
DOI: 10.1016/j.cub.2017.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Vps13D Encodes a Ubiquitin-Binding Protein that Is Required for the Regulation of Mitochondrial Size and Clearance

Abstract: The clearance of mitochondria by autophagy, mitophagy, is important for cell and organism health [1], and known to be regulated by ubiquitin. During Drosophila intestine development, cells undergo a dramatic reduction in cell size and clearance of mitochondria that depends on autophagy, the E1 ubiquitin-activating enzyme Uba1, and ubiquitin [2]. Here we screen a collection of putative ubiquitin-binding domain-encoding genes for cell size reduction and autophagy phenotypes. We identify the endosomal sorting com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
180
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 129 publications
(208 citation statements)
references
References 28 publications
16
180
0
2
Order By: Relevance
“…While this article was under review, Anding et al published findings showing VPS13D to be a ubiquitin‐binding protein affecting mitochondrial fission and fusion, consistent with our findings, and also implemented VPS13D in autophagy, a process that we have recently reported to be involved in ataxia …”
Section: Discussionsupporting
confidence: 91%
“…While this article was under review, Anding et al published findings showing VPS13D to be a ubiquitin‐binding protein affecting mitochondrial fission and fusion, consistent with our findings, and also implemented VPS13D in autophagy, a process that we have recently reported to be involved in ataxia …”
Section: Discussionsupporting
confidence: 91%
“…Yeast Vps13p (homologue of human VPS13A) has a role in mitochondrial stability and possibly impedes mitochondrial autophagy . Recently, Vps13D was shown to play a role in mitochondrial fission, clearance, and autophagy (mitophagy) in Drosophila , and its knockout in human HeLa cells led to enlarged mitochondria . Based on pairwise comparisons between VPS13 gene family members and yeast Vps13p, Velayos‐Baeza et al have identified the UBA domain (amino acid 2637–2673), which confers target specificity to multiple enzymes of the ubiquitination system .…”
Section: Discussionmentioning
confidence: 99%
“…Based on pairwise comparisons between VPS13 gene family members and yeast Vps13p, Velayos‐Baeza et al have identified the UBA domain (amino acid 2637–2673), which confers target specificity to multiple enzymes of the ubiquitination system . This domain is absent from other VPS13 proteins, and Anding et al have shown that this domain is in part responsible for the ability of VPS13D to regulate mitochondrial size . We did find some indications of mitochondrial alterations in muscle biopsy but found normal enzymatic activities in fibroblast cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene is highly intolerant to missense variation and even more so to loss of function variants . VPS13D has recently been shown to be essential for mitochondrial metabolism in Drosophila , including viability, autophagy, and clearance . The gene is also essential in human cell lines, and its deletion leads to abnormal mitochondrial morphology .…”
mentioning
confidence: 99%